Ring-planet mesh stiffness study with different boundary conditions and crack locations - Xue, S.; Howard, Ian (2015)
The ring gear boundary conditions can have a great influence on the ring-planet mesh stiffness. Two different boundary conditions have been compared in this study using the finite element analysis (FEA) method, namely the full constraint condition and the pin-supported condition. Cracks can cause changes in the gear mesh stiffness and the effect of ring gear crack locations has been analysed under both boundary conditions. Multiple crack locations were chosen and especially in the pin-supported model, where the crack locations were between two pin supports. The same ring-planet mesh stiffness change between the healthy model and the cracked model was observed wherever the crack locations were in the full constraint model. However, different ring-planet mesh stiffness changes were observed when the cracks were implanted to different teeth in the pin-supported model. The highest value was observed when the crack was close to the pin support and the lowest value was observed when the crack was in the middle of two pin supports. These observed changes can provide additional information to help identify the locations of the ring gear cracks in the planetary gear when the mounting method makes use of pin-supports.